MODEL PEMBINAAN PENINGKATAN KOMPETENSI PENILIK - Melati Indri Hapsari (Perspektif Ilmu Pendidikan, 2011)
Non-formal education supervisors play an important role in providing and developing quality non-formal education. As their career development is based on their professional performance regulated in a credit system, many of the supervisors face hindrance to complete the requirement with the existing situation. This research introduces a model of supervisor’s competence development resulted from a research conducted in five districts in Central Java involving a number of non-formal education supervisor. The model was developed on the bases of supervisor’s competence mapping.